2020
DOI: 10.1136/ijgc-2020-001834
|View full text |Cite
|
Sign up to set email alerts
|

Are trainees working in obstetrics and gynecology confident and competent in the care of frail gynecological oncology patients?

Abstract: IntroductionOlder patients undergoing cancer surgery are at increased risk of post-operative complications, prolonged hospital stay, and mortality. Identification of frailty can help predict patients at high risk of peri-operative complications and allow a collaborative, multidisciplinary team approach to their care. A survey was conducted to assess the confidence and knowledge of trainees in obstetrics and gynecology regarding identification and management of peri-operative issues encountered in frail gynecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Of note, 77% of the preoperative nurses and 78% of surgeons surveyed had no formal training in identifying and managing frailty. We have previously reported a similar knowledge gap among junior doctors working in gynecological oncology 12. To support recognition of frailty and confidence in formally assessing frailty, undergraduate and postgraduate training needs to be updated to meet the demands of an aging population.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Of note, 77% of the preoperative nurses and 78% of surgeons surveyed had no formal training in identifying and managing frailty. We have previously reported a similar knowledge gap among junior doctors working in gynecological oncology 12. To support recognition of frailty and confidence in formally assessing frailty, undergraduate and postgraduate training needs to be updated to meet the demands of an aging population.…”
Section: Discussionmentioning
confidence: 81%
“…Multiple surveys of healthcare professionals have described barriers to implementing frailty care being multifactorial and include hospital specific institutional issues, healthcare system processes, professional knowledge, and patient/family members wishes 8 12 13. Lack of expertise in the assessment and management of frailty, lack of funding and lack of time were identified as the key barriers to providing targeted care for patients with frailty in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, another study exploring the competence and confidence of trainees working in gynaecological oncology found that 67% of trainees believed they had inadequate training in the perioperative management of older patients with or without frailty [52]. Most of these trainees valued closer collaboration with geriatrics when managing older patients.…”
Section: Undergraduate and Postgraduate Experiences And Perspectivesmentioning
confidence: 99%